Optimizing the Role of National Unity and Political Bodies in Supervising Mass Organizations and Fostering Pancasila Values, National Insight and Moderate Values ​​in Soppeng Regency - Mirwan Fikri Muhkam; Muspita Sari; M Asyhari Rasyid; Andi Risa Aulia Nur Putri Faizal; Yusuf Djabbar (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to examine the role of Kesbangpol in efforts to foster and supervise community organizations, examine the synergistic relationship between the government, political actors and community organizations as well as its social impact on society. The method used in this research is descriptive qualitative with a research strategy, namely case studies, which has an impact on the intensity of socialization of Pancasila values and national insight by collaborating with related agencies to mature citizens' understanding of how to have a society, nation and state that are in line with ideals. and Indonesia's national goal, which in its concrete form is to hold a "Pancasila Village" (2) Kesbangpol Service as a forum for ensuring the values of moderation in society which is demonstrated through its role as a forum for complaints about beliefs adhered to by individuals and community organizations through the synergy of partnerships with the Soppeng Regency Community Understanding Institute (Pakem).